Implementation Student Learning Achievement for Student: Literature Review - Usmar, Usmar; Sismiati, Sismiati; Sulaiman, Syarifuddin (Dinasti Publisher, 2024)
The purpose of this article is to investigate and describe the role of intrinsic factors and motivation in student learning achievement and explain how students' internal characteristics (intrinsic factors) and drive to learn (motivation) are interrelated and how these interactions affect their learning outcomes with a literature review. This article uses qualitative methods with a literature review for the implementation of Intrinsic Factors, Motivation, and Intrinsic Factors, Motivation, Student Learning Achievement. Innate and motivational factors play a fundamental role in the realm of education, shaping the path of student learning achievement. Identifying and leveraging these factors can enhance the learning journey, allowing students to maximize their academic capabilities. The complex interaction between intrinsic factors and motivation serves as the basis of student achievement. Acknowledging and fostering students' internal attributes, coupled with creating a motivating environment according to their unique needs, is essential to unlocking their full academic potential. The recommendations given in this article are in the form of views that are expected to create an educational environment that supports students' development holistically, motivates them to learn, and helps them reach their full academic potential.